دراسة تحليلية للتحديات الداخلية والخارجية التي تواجه القطاع الصناعي في سـورية (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى تحليل التحديات الداخلية والخارجية التي تواجه قطاع الصناعة السورية، حيت تتمثل التحديات الداخلية، بالتحديات التي تصدر عن المجتمع السوري نفسه والاقتصاد السوري نفسه، وهي: انخفاض دور النفط كمصدر أساسي لتوفير القطع الأجنبي، والزيادة السكانية، إضافةً إلى التحدي التكنولوجي. أما بالنسبة للتحديات الخارجية التي تواجه القطاع الصناعي في سورية فهي تحديات تفرض عليه باعتباره جزءاً من الاقتصاد السوري للعمل بشكل مكثف باتجاه زيادة قدرته التنافسية في الأسواق المحلية والعالمية. وتتمثل هذه التحديات بالعولمة وفرض الاندماج بالاقتصاد العالمي، وتحدي الشراكة السورية الأوربية، وتحدي زيادة القدرة التنافسية للمنتجات الصناعية السورية عالمياً، إضافةً إلى التحدي الأمني. وتؤثر هذه التحديات بشكل كبير على القطاع الصناعي في سورية وفي قدرته على أداء دوره في عملية التنمية. This research aims to analyze the internal and external challenges facing The Syrian Industrial Sector.  Internal challenges are those originated by both the Syrian society and the Syrian economy, and these challenges are: the decline in the role of oil as the primary source for the provision of foreign exchange, population growth, and in addition to the technological challenge . The external challenges are imposed on the Syrian industrial sector as it is a  part of the Syrian economy, in order  to work intensively to  increase  its competitiveness in domestic and global markets. These challenges emerge due to globalization,  integration into the global economy, the challenge of the Syrian European partnership,  the challenge of increasing the competitiveness of the Syrian industrial products globally, along with the security challenge. These challenges influence the industrial sector in Syria on a large scale and weaken its ability to fulfill its role in the development process.